Synthesis, Biological Evaluation, and SAR Studies of 14β-phenylacetyl Substituted 17-cyclopropylmethyl-7, 8-dihydronoroxymorphinones Derivatives: Ligands With Mixed NOP and Opioid Receptor Profile - Kumar, Vinod; Polgar, Willma E.; Cami-Kobeci, Gerta; Thomas, Mark P.; Khroyan, Taline V.; Toll, Lawrence; Husbands, Stephen M. (Frontiers in Psychiatry, 2018)
A series of 14β-acyl substituted 17-cyclopropylmethyl-7,8-dihydronoroxymorphinone compounds has been synthesized and evaluated for affinity and efficacy for mu (MOP), kappa (KOP), and delta (DOP) opioid receptors and nociceptin/orphanin FQ peptide (NOP) receptors. The majority of the new ligands displayed high binding affinities for the three opioid receptors, and moderate affinity for NOP receptors. The affinities for NOP receptors are of particular interest as most classical opioid ligands do not bind to NOP receptors. The predominant activity in the [35S]GTPγS assay was partial agonism at each receptor. The results are consistent with our prediction that an appropriate 14β side chain would access a binding site within the NOP receptor and result in substantially higher affinity than displayed by the parent compound naltrexone. Molecular modeling studies, utilizing the recently reported structure of the NOP receptor, are also consistent with this interpretation.